Effect of Renal and Hepatic Impairment on the Pharmacokinetics of Temsavir, the Active Moiety of Fostemsavir. (18th January 2021) - Magee, Mindy; Slater, Jill; Mannino, Frank; Ackerman, Peter; Llamoso, Cyril; Moore, Katy
Abstract: The oral prodrug fostemsavir (GSK3684394, formerly BMS‐663068) is an antiretroviral treatment for HIV‐1. Fostemsavir is metabolized to its active moiety, temsavir, a first‐in‐class HIV‐1 attachment inhibitor that binds to the viral envelope glycoprotein 120. Long‐term antiretroviral therapy, the resulting longer life expectancy, and/or certain coinfections can increase the risk of chronic liver and kidney disease in HIV‐1–infected individuals. Two studies were conducted to collectively evaluate the impact of renal and hepatic impairment on temsavir pharmacokinetics (PK) and safety following a single dose of a 600‐mg extended‐release fostemsavir tablet. There was no clinically meaningful effect of renal or hepatic impairment on temsavir PK, although renal clearance decreased with increasing renal impairment from moderate to severe, and exposure (maximum concentration and area under the plasma concentration–time curve from time 0 to infinity) tended to increase with increasing severity of hepatic impairment. No clinically meaningful effect of hemodialysis on temsavir PK parameters was observed. Fostemsavir was generally safe and well tolerated by treated subjects. Most adverse events (AEs) were mild, with the exception of 1 patient in the renal impairment study who discontinued due to 2 serious AEs unrelated to the study drug. No other treatment‐emergent serious AEs occurred, and no other AEs leading to discontinuation were reported. Overall, these results suggest that fostemsavir can be used without dose modification in subjects with mild to severe renal impairment, including those with end‐stage renal disease on hemodialysis, and in subjects with mild to severe hepatic impairment.